A Preliminary Study on Characterizing Syntactic Processing and Pause Patterns in Bilingual English-Bahasa Indonesia Specific Language Impairment - Anjarningsih, Harwintha Y.; Huda, Nurul; Kirana, Angkita Wasito (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
A 12-year-old boy received a diagnosis of an unspecified